1997
DOI: 10.1002/(sici)1096-8628(19970613)70:3<284::aid-ajmg13>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal malrotation in a child with cardio-facio-cutaneous syndrome

Abstract: We present a child with cardio-facio-cutaneous (CFC) syndrome with inadequate weight gain due to inadequate food intake. After correction of hyperemesis due to intestinal malrotation, she continued to fail to feed due to poor suck reflex. A review documented digestive system findings in 26 of 57 reported patients with CFC syndrome. Thus, digestive system dysfunction and malformation may represent an additional manifestation of the CFC syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Gastroenterologists can differentiate the constipation caused by intestinal dysmotility from other less common conditions such as intestinal malrotation, functional megacolon, anal stenosis, or rarely intestinal atrophy. 41,44,57 Constipation can continue into adulthood and follow-up by a gastroenterologist may be helpful in planning a satisfactory bowel regimen.…”
Section: Gastrointestinal and Growth Issuesmentioning
confidence: 99%
“…Gastroenterologists can differentiate the constipation caused by intestinal dysmotility from other less common conditions such as intestinal malrotation, functional megacolon, anal stenosis, or rarely intestinal atrophy. 41,44,57 Constipation can continue into adulthood and follow-up by a gastroenterologist may be helpful in planning a satisfactory bowel regimen.…”
Section: Gastrointestinal and Growth Issuesmentioning
confidence: 99%
“…28 Additional digestive system findings include hepatomegaly, umbilical hernia, inguinal hernia, anal stenosis and intestinal malrotation. 52 …”
Section: Gastrointestinal Tractmentioning
confidence: 99%
“…Somer et al [1992] reviewed 13 of the cases and added three other patients. Other cases were reported from Europe [Blanchet-Bardon et al, 1991;Bottani et al, 1991;Corsello and Giuffrè, 1991;Della Monica et al, 1991;Fryer et al, 1991;Fryns et al, 1991Fryns et al, , 1992Ghezzi et al, 1992;Turnpenny et al, 1992;Borradori and Blanchet-Bardon, 1993;Ward et al, 1994;Krajewska-Walasek et al, 1996;Manoukian et al, 1996;Wieczorek et al, 1997], North America [Lopez-Rangel et al, 1993;Mathews et al, 1993;Raymond and Holmes, 1993;Young et al, 1993;Leichtman, 1996;McDaniel and Fujimoto, 1997;Grebe and Clericuzio, 2000;Rauen et al, 2000], and Australia [Ades et al, 1992]. Other cases described before 1986 as variants of Noonan syndrome have been considered to be examples of CFC syndrome: five cases reported by Pierini and Pierini [1979], according to Neri et al [1991]; four cases described by Cantú et al [1982], according to Bottani et al [1991] and Raymond and Holmes [1993]; one patient reported by Navaratnam and Hodgson [1973], according to Fryer et al [1991] and Mathews et al [1993]; and one patient described by Neild et al [1984], according to Borradori and Blanchet-Bardon [1993].…”
Section: Introductionmentioning
confidence: 99%